EFEK QUALITY OF WORK LIFE DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI EKSTERNAL SEBAGAI VARIABEL INTERVENING - Okta Letami; Dheo Rimbano; Nasruddin Nasruddin; Yuli Eprianti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
This study examines the influence of Quality of Work Life and work culture on employee performance at the Office of the Regional Development Planning Agency, Research and Development of Lubuklinggau City with external motivation as an intervening variable. This study uses a quantitative method with a sample of 41 employees. The results of the study indicate that Quality of Work Life and work culture have a significant impact on employee performance, while external motivation strengthens the relationship. This study provides recommendations for strategies for developing Quality of Work Life, work culture and external motivation to improve employee performance.